Composition of Advances in the District Central Cooperative Banks in Punjab - Goel, Priya; Pathak, Dr. Devender (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The Banking scene in India has undergone a tremendous change due to the Narsimham Committee recommendations since 1992 i.e. with the advent of the new economic policy. It emphasized shift from centralized planning to indicative planning. Thus the committee shifted its onus from ownership to efficiency and competitiveness while ensuring the integrity and operational autonomy of the banks. Financial sector reforms, based on Narsimham committee recommendations, aim at fostering financially strong banking cooperative in a competitive world. As a result of these financial sector developments, policy makers and social thinkers were apprehensive that cooperative banking sector will be facing the challenges of increasing competition, emerging opportunities and withdrawal of government support and may have to abandon its social objectives. But cooperative banking system has some inherent strength in the form of its reach, infrastructure and intimate relations with its customers which have strengthened these banks to make a vital contribution to nations development. Cooperative banking system has progressively matured and is preparing itself to successfully meet new challenges. This paper is focused on one of the main business areas of the District Central Cooperative Banks of Punjab i.e. composition of advances. In this paper, a brief outline has been given about the various loan schemes of the District Central Cooperative Banks and the total loans outstanding in different categories of loans advanced during the period of study i.e. from 2000 to 2010.